2017
DOI: 10.5194/acp-2017-1007
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

How important are future marine and shipping aerosol emissions in warming Arctic summer and autumn?

Abstract: Abstract. Future sea ice retreat in the Arctic in summer and autumn is expected to affect both natural and anthropogenic aerosol emissions: sea ice acts as a barrier between the ocean and the atmosphere, and reducing it increases dimethyl sulphide and sea salt emissions. A decrease in the area and thickness of sea ice could in addition lead to enhanced Arctic ship traffic, e.g. to shorten the paths of cargo ships. Changes in the emissions of aerosol particles can then influence cloud properties, precipitation,… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(34 citation statements)
references
References 43 publications
1
33
0
Order By: Relevance
“…Whereas the Chakrabarty et al 16 data are not significantly different from ours, the tar brC observed by Alexander et al 15 appears to be more mature than that observed in our study, according to its lower AAEs of~2. Greater maturity is 11,12 ). The BC and tar brC AAEs and MAEs were retrieved from the data of Fig.…”
Section: Optical Model Of Hfo-pm Tarmentioning
confidence: 99%
See 2 more Smart Citations
“…Whereas the Chakrabarty et al 16 data are not significantly different from ours, the tar brC observed by Alexander et al 15 appears to be more mature than that observed in our study, according to its lower AAEs of~2. Greater maturity is 11,12 ). The BC and tar brC AAEs and MAEs were retrieved from the data of Fig.…”
Section: Optical Model Of Hfo-pm Tarmentioning
confidence: 99%
“…11 Fundamental differences in physical properties also impact the interpretation of fundamental LAC measurements and treatment in model simulations. 12 Insoluble LAC species include BC as well as the "tar ball" brC previously identified by electron microscopy in wildfire and biomass-burning samples, [13][14][15][16][17][18] which has fundamentally different properties to both BC and soluble brC. It is therefore essential to understand the chemical nature of LAC in HFO-PM in order to predict its environmental impacts and atmospheric mixing state, and to develop analytical techniques suitable for its quantification.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Arctic regions are largely a marine, or coastal marine, environment beginning in late spring and extending into the autumn. Increases in PMA production are expected in the future from the increasingly exposed ocean surface as sea ice retreats (Browse et al, ; Gilgen et al, ; Struthers et al, ) and with the increased presence of first year ice that is thin and prone to fracturing (Maslanik et al, ; Overland & Wang, ; Stroeve et al, ). As discussed in section , sea salt concentrations peak in the winter–spring at ground stations, and areas of open water (i.e., leads, polynas) in ice‐covered regions are likely contributors to PMA during this time of year (e.g., Deshpande & Kamra, ; Kirpes et al, ; Leck et al, ; May et al, ; Nilsson et al, ; Scott & Levin, ; Weinbruch et al, ).…”
Section: Regional Arctic Processesmentioning
confidence: 99%
“…Using chemical transport and radiative forcing models, Dalsøren et al () found warming under two spatially explicit emission scenarios (Peters et al, ) between 2004 and 2030, while Fuglestvedt et al () used a simple 2‐box climate model to demonstrate enhanced Arctic warming from short‐lived shipping pollutants until 2160. In contrast, Gilgen et al () found net cooling by 2050 using a global aerosol‐climate model, driven by enhanced cloud droplet number and optical thickness of clouds over the Arctic Ocean. Although highly relevant to environmental impacts of future shipping, the methods and emission projections used previously are not capable of evaluating dynamic feedbacks in the physical climate and human activities.…”
Section: Introductionmentioning
confidence: 91%